2005
DOI: 10.1590/s1519-69842005000200006
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity assessment of benthic macroinvertebrates along a reservoir cascade in the lower São Francisco river (northeastern Brazil)

Abstract: In order to verify the cascade-system effect in benthic macroinvertebrate communities, and the implications for policy making and proposals for conservation and sustainable use of the lower portion of São Francisco river basin (Bahia State, Brazil), a three-reservoir cascade system including two stretches downstream were studied during dry (June, 1997) and rainy (March, 1998) periods. The dominant groups found were Mollusca (Melanoides tuberculata), Oligochaeta, and Chironomidae larvae. Low Shannon-Wiener and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 10 publications
1
38
1
6
Order By: Relevance
“…Thus, the use of an inappropriate sampler to collect mollusks seems to not have affected knowledge of the diversity of the Contas River malacofauna. The results obtained in this study also concord with the findings of the few available studies on the macroinvertebrate communities of semiarid rivers in the Brazilian Northeast region, in which insects are the most diversified and abundant group, but mollusks are also frequent, with some dominant taxa such as the invasive M. tuberculata (Maltchik 1999, Callisto et al 2005, Andrade et al 2008, Santana et al 2009). On the other hand, it should be expected that mollusk richness in tropical semiarid regions, where the dry period is prolonged and creates adverse conditions for the freshwater malacofauna, will be smaller than the mollusk richness in regions with more permanent waterbodies.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the use of an inappropriate sampler to collect mollusks seems to not have affected knowledge of the diversity of the Contas River malacofauna. The results obtained in this study also concord with the findings of the few available studies on the macroinvertebrate communities of semiarid rivers in the Brazilian Northeast region, in which insects are the most diversified and abundant group, but mollusks are also frequent, with some dominant taxa such as the invasive M. tuberculata (Maltchik 1999, Callisto et al 2005, Andrade et al 2008, Santana et al 2009). On the other hand, it should be expected that mollusk richness in tropical semiarid regions, where the dry period is prolonged and creates adverse conditions for the freshwater malacofauna, will be smaller than the mollusk richness in regions with more permanent waterbodies.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the construction of dams can cause profound negative effects on aquatic biodiversity because the natural seasonal patterns to which the fauna has adaptations is altered, and normal seasonal migration paths (drifts) are blocked (Rosenberg et al 2000). Callisto et al (2005) observed that reservoirs in cascades cause significant changes in the original continuum of a river, altering the thermal heterogeneity, the connectivity, the fine and the coarse particulate organic matter rates. These changes can lead to significance effects on the communities of invertebrates, causing loss of aquatic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it causes loss of habitats and diversity due to geomorphologic adjustment of the river system toward a new equilibrium condition (Petts and Greenwood, 1985). These impacts are increased when dams are built in series (Barbosa et al, 1999;Callisto et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gastropod M. tuberculatus shows great adaptability to different ecological conditions, but its successful establishment is frequently associated with eutrophic environments (Martins- Silva and Barros, 2001;Callisto et al, 2005;Giovanelli et al, 2005;Vidigal et al, 2005;Rocha-Miranda and Martins-Silva, 2006). Areas located near the Rio Doce State Park in the state of Minas Gerais, which are impacted by eucalyptus plantations, were also favourable for the development of high densities of this species (Vidigal et al, 2005).…”
Section: Discussionmentioning
confidence: 99%